A rare case of pemphigus vulgaris in pregnancy: Challenge in management - Batubara, Irwan Saputra (Journal of Pakistan Association of Dermatologists, 2022)
Pemphigus vulgaris (PV) is an autoimmune bullous disease manifested as flaccid blisters and extensive erosions of the skin and mucous membranes. Pemphigus vulgaris before or during pregnancy is uncommon, with only 36 cases were reported in current English literature between 1966 and 2014. Management of PV includes immunosuppressive, intravenous immunoglobulins, or biologic agents. Currently, there is no published guideline in the treatment of PV in pregnancy. A 22-year-old pregnant woman at 13 weeks of gestation presented with skin erosions and blisters that worsen for 2 months before hospital admission. Dermatological examination revealed painful erosions and blisters with positive Nikolsky signs on the entire body and numerous oral ulcers accompanied by dysphagia and difficulties in eating. Histopathological examination showed suprabasal clefts filled with acantholytic cells extending to hair follicle units consistent with pemphigus vulgaris. She had been managed with systemic corticosteroid under obstetrician supervision, antibiotic, and supportive care. Her condition was significantly improved over the first month of medical treatment. Pemphigus vulgaris in pregnancy is a challenging case due to the course of the disease itself and the complications of long-term use of the therapeutic agents to both maternal and fetal. Without proper treatment, PV may be fatal due to dehydration and secondary bacterial infections. Patients with PV in pregnancy should be monitored intensively with a multidisciplinary approach to obtain a good outcome for the maternal and the baby.